(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The progress of a nation is a function of thelevel of the resourcefulness of the people which to a great extent, relates tothe level of quality of the training and purposeful development of education inthat nation. Such progress or development could only occur when an individualin the society is gainfully employed and per capital income is enhanced.Entrepreneurship education is a means through which government could attainsuch development in the society. Therefore, this paper examines how the role ofentrepreneurship education and how it could help in job creation in MadhyaPradesh.